Comparative analysis of upward/downward filtration and expression using a consolidation cell - Ishii, Takeshi; Fukuyama, Ryo; Tanaka, Takanori; Jami, Mohammed Saedi; Iwata, Masashi (2014)
Filtration behavior is influenced by particle settling in a slurry. In a downward filtration, an additional cake derived from settling particles increases filtration resistance. In an upward filtration, on the other hand, the particle settling leads to dilute the slurry near the filter medium, resulting in a decrease of filtration resistance. Iritani et al. have proposed an analytical method for filtration considering the effects of particle settling [1]. When a slurry is filtered in a consolidation cell which has upper and lower drainage surfaces (Fig.1), both phenomena mentioned above seem to occur simultaneously. In this study, the validity of the filtration properties obtained from expression test using the consolidation cell were examined.